The Effect of Canva-Based Animated Video Media on Integrated Science and Social Studies Learning Outcomes: A Quasi-Experimental Study in Indonesian Elementary Education - Intan Nur Alini; Nashrullah Nashrullah; Muchdar Muchdar; Abdul Rahman; Sukri Sukri (Journal of Innovation and Research in Primary Education, 2026)
This quasi-experimental study investigated the influence of Canva-based animated video media on fifth-grade students' IPAS (Integrated Science and Social Studies) learning outcomes at SDN 2 Dolo. Employing a nonequivalent control group design, the research involved 60 students divided into experimental (n=34) and control (n=26) groups. The experimental group received instruction using Canva-based animated videos integrating visual animations, text, and audio narration, while the control group experienced conventional teacher-centered methods. Data were collected through validated multiple-choice tests (15 items, reliability α=0.788) administered as pretests and posttests. Descriptive statistics and independent samples t-test were employed for data analysis using IBM SPSS Statistics 25. Results revealed that the experimental group achieved significantly higher posttest scores (M=84.41, SD=8.941) compared to the control group (M=78.08, SD=9.389), with statistical significance confirmed (t=2.661, p=0.010<0.05). These findings demonstrate that Canva-based animated video media significantly enhances IPAS learning outcomes by promoting student engagement, attention, and conceptual understanding. The study contributes empirical evidence supporting multimedia learning theory in integrated curriculum contexts and validates accessible digital tools' effectiveness in resource-constrained educational settings. Future research should examine long-term retention effects and optimal animation design features across diverse educational contexts.